FAKTOR-FAKTOR YANG MEMENGARUHI KETEPATAN WAKTU PELAPORAN KEUANGAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2015-2017 - Vivi Lana Aprianti, 15.05.52.0295; Nuswandari, Cahyani (Students' Journal of Accounting and Banking, 2019)
This research is a study that tests and analyzes the effect of firm size, managerial ownership, profitability, leverage, liquidity, and reputation of KAP on the timeliness of financial reporting. This research was conducted at manufacturing companies listed on the Indonesia Stock Exchange. This study used a purposive sampling method in sample selection using the sample criteria as manufacturing companies listed on the Indonesia Stock Exchange during the period 2015-2017. Based on the criteria, a sample of 297 companies was obtained during the three-year observation period. The analytical tool used is Logistic Regression. The results of the study indicate that the variable firm size and liquidity have a significant positive effect on the timeliness of financial reporting. Managerial ownership, profitability and leverage variables have a positive and not significant effect on the timeliness of financial reporting. KAP reputation variables have a negative and not significant effect on the timeliness of financial reporting.